PENINGKATAN EFEKTIVITAS BELAJAR TOLAK PELURU MELALUI PENGGUNAAN MEDIA PELURU TIRUAN DARI BOLA PLASTIK PADA SISWA KELAS VI SEMESTER 1 SDN BABADAN DEMAK - Mardiwon, Mardiwon (Universitas Muria Kudus, 2016)
This research is motivated less availability of instructional media shot put. So it needs to bereplaced with another form of media-made bullets. The study design used is classroom actionresearch. After carrying out repairs learning, student achievement is increasing both the firstcycle and the second cycle. The results showed that (a) the activity of pre-cycle students by 50%,the first cycle of 70%, then the second cycle by 80% this means that there is an increase of 20%and 10%; (B) the activities of teachers by 75% pre-cycle, the first cycle is 95%, then the secondcycle of 100% means there is an increase of 20% and 5%; (C) The results of student learningprasiklus son reaches 59%, the first cycle is 95%, then the second cycle of 100%; whereas femalestudent learning outcomes pre-cycle reaches 41%, the first cycle of 79%, then the second cycle of79%; and whereas (d) Response (Level of Satisfaction Study) students, achieve student responserate of 85%, has the following criteria Very Satisfied. This criterion illustrates that students reallyhappy and really enjoyed the process of learning.